2015
DOI: 10.2106/jbjs.cc.n.00242
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Cobalt Toxicity: Bearing the Brunt of a Failed Ceramic Liner

Abstract: This case supports previous reports of cobalt toxicity secondary to catastrophic third-body wear of a CoCr femoral head following a fractured ceramic bearing. It also demonstrates the potential reversibility of many systemic sequelae associated with cobalt toxicity. To our knowledge, this case represents the highest documented blood cobalt level (45,840 nmol/L).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Also, trunnionosis [1], defined as wear of the femoral head-neck interface, has recently been acknowledged as a growing cause of THA failure and source of metallosis. Third-body wear affecting exclusively the bearing surface due to previous ceramic fracture had been described before [2,3], and some of these reports have also mentioned metal ion levels leading to patient death due to systemic toxicity [4,5]. However, the extensive local inflammatory response with associated abductor destruction is sparsely highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Also, trunnionosis [1], defined as wear of the femoral head-neck interface, has recently been acknowledged as a growing cause of THA failure and source of metallosis. Third-body wear affecting exclusively the bearing surface due to previous ceramic fracture had been described before [2,3], and some of these reports have also mentioned metal ion levels leading to patient death due to systemic toxicity [4,5]. However, the extensive local inflammatory response with associated abductor destruction is sparsely highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…The composite score for ocularvestibular symptoms increased from 54% to 57%-68% with rising threshold value (120-170 or 220 nmol/L), which suggests a correlation between ion concentration and symptomprevalence. Subjects in the current study reported tinnitus and hearing loss far more often than patients in the general population [53,56,57]. Also, more subjects were found with tinnitus in the high cobalt ionconcentration group at higher thresholds and with increasing threshold values.…”
Section: Cobalt Toxicitymentioning
confidence: 54%
“…These concentrations might be influenced by a variety of parameters, which can be divided into patient factors (female sex, age at surgery (young), time since implantation), implant factors (bilateral, small femoral HRA components, design, type of implant (HRA/LHMoM)) and surgical factors (acetabular component malposition, reduced contact patch to rim distance) [55]. There was a concern that increased cobalt and chromium ion concentrations increased the risk for cancer, but this was proven otherwise in large comparative studies [56,57]. Nevertheless, in 2012, the NetherlandsOrthopaedicAssociation (NOV) advised against the use of any MoM hip arthroplasty [58,59].…”
Section: Metal-on-metal Issuesmentioning
confidence: 99%